2018
DOI: 10.3389/fphys.2018.00295
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotubes and Other Engineered Nanoparticles Induced Pathophysiology on Mesothelial Cells and Mesothelial Membranes

Abstract: Nanoparticles have great potential for numerous applications due to their unique physicochemical properties. However, concerns have been raised that they may induce deleterious effects on biological systems. There is accumulating evidence that, like asbestos, inhaled nanomaterials of >5 μm and high aspect ratio (3:1), particularly rod-like carbon nanotubes, may inflict pleural disease including mesothelioma. Additionally, a recent set of case reports suggests that inhalation of polyacrylate/nanosilica could in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 111 publications
0
13
0
Order By: Relevance
“…It is plausible that inflammation precedes tumorigenesis, and tumorigenesis and inflammation co-occur during the chronic stage after exposure. Indeed, a number of studies have demonstrated the co-existence of inflammation and malignancy in CNT-exposed animals, suggesting an association between inflammation and cancer induced by CNTs (Tables 1 and 2) (Kuempel et al 2017; Sinis et al 2018). For instance, when directly instilled into the pleural cavity of mice, long MWCNTs with the length of 85% fibers more than 15 μm, which are similar to long fiber amosite asbestos, resulted in chronic inflammation and mesotheliomas in the pleura (Chernova et al 2017).…”
Section: The Interplay Among Cnt-induced Pathological Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is plausible that inflammation precedes tumorigenesis, and tumorigenesis and inflammation co-occur during the chronic stage after exposure. Indeed, a number of studies have demonstrated the co-existence of inflammation and malignancy in CNT-exposed animals, suggesting an association between inflammation and cancer induced by CNTs (Tables 1 and 2) (Kuempel et al 2017; Sinis et al 2018). For instance, when directly instilled into the pleural cavity of mice, long MWCNTs with the length of 85% fibers more than 15 μm, which are similar to long fiber amosite asbestos, resulted in chronic inflammation and mesotheliomas in the pleura (Chernova et al 2017).…”
Section: The Interplay Among Cnt-induced Pathological Effectsmentioning
confidence: 99%
“…In these scenarios, the newly synthesized fibrotic ECM from fibrosis creates a tumorigenic microenvironment that boosts tumorigenesis in CNT-deposited tissues, and tumor progression and metastasis in nearby and distal tissues, respectively. Notably, MWCNTs that induce severe fibrosis have a higher capability to induce tumorigenesis than those that cannot, or only slightly, induce fibrosis (Kuempel et al 2017; Sinis et al 2018). For instance, intraperitoneal injection of MWNT-7 induced fibrosis on the liver surface in rats 1-month post-exposure, whereas injection of tangled MWCNTs did not.…”
Section: The Interplay Among Cnt-induced Pathological Effectsmentioning
confidence: 99%
“…A number of studies in plants have identified that CNTs can accumulate in the roots and leaves of plants and induce oxidative stress and photosynthetic defects . Similar oxidative and cellular stress effects have been observed in mammalian cells in vitro . There is also preclinical evidence that inhalation of CNTs and other carbon nanomaterials, such as CNFs, can form fiber‐like shapes that can result in pulmonary diseases similar to asbestos exposure, such as mesothelium .…”
Section: Toxicity Of Carbon Nanomaterialsmentioning
confidence: 82%
“…Among the highly expressed genes, COX-2 is mainly associated with cell proliferation and inhibition of apoptosis [ 165 , 166 , 167 ]. Many other inflammatory genes such as TNF-α, IL-8 and IL-1β are also regulated after exposure to CNTs and other long fibers [ 168 , 169 ]. In a comprehensive study on the effects of pulmonary exposure to 10 commercial MWCNTs, Poulsen and co-workers found that inflammation and genotoxicity were related to dose, time and physicochemical properties [ 170 ].…”
Section: Do Asbestos and Cnts Have The Same Mechanism Of Pathogenicity?mentioning
confidence: 99%